1997
DOI: 10.1053/jlts.1997.v3.ajlts0030659
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Techniques Are Not Important In Directing Blood Product Transfusion During Liver Transplantation

Abstract: Preoperative acquired clotting parameters such as prothrombin time, activated partial thromboplastin time, antithrombin III, platelet concentration, and fibrinogen show coagulopathy caused by insufficiency of the diseased liver. Intraoperative determination of clotting factors or parameters is not helpful to direct intraoperative transfusion of blood, blood components, or platelets because transfusions performed solely for correction of clotting data do not correlate with the real intraoperative requirements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This observation supports the principle that blood component use during LT should be based on clinical assessment and a well-established transfusion protocol, rather than laboratory tests. 17,18 Because of the low blood cell volume transfused in our patients, we believe use of intraoperative autotransfusion would increase the complexity of LT without adding great advantages. Groups that use intraoperative autotransfusion have reported greater transfusion rates than ours.…”
Section: Discussionmentioning
confidence: 99%
“…This observation supports the principle that blood component use during LT should be based on clinical assessment and a well-established transfusion protocol, rather than laboratory tests. 17,18 Because of the low blood cell volume transfused in our patients, we believe use of intraoperative autotransfusion would increase the complexity of LT without adding great advantages. Groups that use intraoperative autotransfusion have reported greater transfusion rates than ours.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased use of component therapy resulted in the same number of donor exposures for the recipient (Kang et al, 1985). The absence of guidelines and any clear evidence as to the most appropriate thresholds has left questions with regard to the clinical use of algorithm-based replacement therapy in hepatic surgery (Reyle-Hahn & Rossaint, 1997).…”
Section: Hepatic Surgerymentioning
confidence: 99%
“…During the recipient hepatectomy measurement and prophylactic treatment of abnormal laboratory bleeding time (BT), PT, INR, and aPTT have been common practice in order to help control anticipated surgical bleeding. However, as early as 1997, it was identified that aggressively correcting laboratory coagulation abnormalities prior to the anhepatic phase of transplantation is not required and that over-resuscitation during the pre-anhepatic phase may lead to extensive blood loss [91]. Prophylactic administration of FFP and RBCs contributes to blood loss by increasing splanchnic pressure in an already hyperdynamic circulatory state.…”
Section: Intraoperative Preparation Of a Critically Ill Recipient For Liver Transplantmentioning
confidence: 99%